An Open Services Regime Recipe for Jobless Growth? - Suparna Karmakar (Indian Council for Research on International Economic Relations (ICRIER), 2008)
Development economists' disfavour with services as a viable engine of growth has been expressed both through theoretical and empirical analysis. One of the stylized facts of development economics is that share of services in employment increases only with the rise in per capita incomes. The skepticism emanates from the observed relatively jobless nature of service sector growth, in particular in the low- and middle-income developing countries. However, given that services have becomes the main source of growth in even the lowest-income developing countries, new empirical evaluation of this thesis has become crucial. A second stylized fact openly acknowledges trade as a source of growth and development. International trade in services, and in particular in the developing countries, has remained significantly lower in comparison to its share in global output. Further, one of the notable trends in recent years has been the increasing importance of cross-border supply of services in economic activities of countries. But is this a sustainable and viable model of development? In view of the above, this paper reviews India's experience to understand how services sector liberalisation can generate (welfare) gains for developing countries, in particular vis–vis its employment generation potential. The analysis has been based on India's experience of an increasingly open service sector and reviews the different channels through which economic gains are garnered from openness to trade in services. But the lessons from this analysis extend far beyond India and are of interest to both developed and developing countries' policymakers concerned about sustaining the competitiveness of their domestic economy. ic activities of countries. But is this a sustainable and viable model of development? In view of the above, this paper reviews India's experience to understand how services sector liberalisation can generate (welfare) gains for developing countries, in particular vis–vis its employment generation potential. The analysis has been based on India's experience of an increasingly open service sector and reviews the different channels through which economic gains are garnered from openness to trade in services. But the lessons from this analysis extend far beyond India and are of interest to both developed and developing countries' policymakers concerned about sustaining the competitiveness of their domestic economy.
Keywords: 330; Dienstleistungshandel; Handelsliberalisierung; Wirtschaftswachstum; Beschäftigungseffekt; Globalisierung; Internationaler Wettbewerb; Dienstleistungssektor; Indien